Representasi Tokoh Wanita pada Kisah Fiksi Kriminal: Serial Televisi Sherlock BBC (2010) - Maully, Gevintha Karunia (UI Scholars Hub, 2014)
Sherlock BBC (2010) is one of the latest adaptations of Sherlock Holmes. By using the modern era as its sett ing, Sherlock off ers something diff erent compared to previous Sherlock Holmes adaptations. This research focuses on the representation of female characters on Sherlock according to an issue that already chosen which is women and crime. The theories and concepts which are used on this research are gender construction in Victorian Era, the concept of femme-fatale and crime fi ction characteristics. I argue that there are some substantial diff erences of female characters’ representation in Sherlock compared to the original story. Despite those diff erences, female characters in Sherlock are still represented in a similar manner as the crime fi ctions characteristics in which women are always put in an inferior position and the one who need men’s help.